The Effectiveness of A Mentoring-Based Supervision Approach to Strengthen The Psychological Bond Between Supervisors and Teachers - Agus; Rukmana Arahmin; Mawardi Djamaluddin Ari (Jurnal Progress: Wahana Kreativitas dan Intelektualitas, 2025)
Improving educational quality requires comprehensive and integrated institutional management, and one effective way to enhance school quality is through supervision that supports teacher performance. This study examines the effectiveness of a mentorship-based supervision approach in strengthening the psychological bond between supervisors and teachers in Islamic high schools in North Maluku Province. Using a quasi-experimental posttest-only control group design, data were collected through pretests and posttests from two groups: the School Supervisor Working Groups at the Ministry of Religious Affairs Offices in Tidore Islands City and Ternate City. Data analysis included normality and homogeneity tests, the Wilcoxon Signed Rank Test, the Mann-Whitney U Test, and the N-Gain test. The findings show that the experimental group achieved an average N-Gain score of 56.69% (fairly effective), while the control group achieved 44% (less effective). These results indicate that the mentorship-based supervision approach is moderately effective in strengthening the psychological bond between supervisors and teachers during the supervision process.